Benchmark investigation of diamondoid-functionalized electrodes for nanopore DNA sequencing. (8th September 2016) - Sivaraman, Ganesh; Amorim, Rodrigo G; Scheicher, Ralph H; Fyta, Maria
Abstract: Small diamond-like particles, diamondoids, have been shown to effectively functionalize gold electrodes in order to sense DNA units passing between the nanopore-embedded electrodes. In this work, we present a comparative study of Au(111) electrodes functionalized with different derivatives of lower diamondoids. Focus is put on the electronic and transport properties of such electrodes for different DNA nucleotides placed within the electrode gap. The functionalization promotes a specific binding to DNA leading to different properties for the system, which provides a tool set to systematically improve the signal-to-noise ratio of the electronic measurements across the electrodes. Using quantum transport calculations, we compare the effectiveness of the different functionalized electrodes in distinguishing the four DNA nucleotides. Our results point to the most effective diamondoid functionalization of gold electrodes in view of biosensing applications.